Research on Population Trends and Optimal Allocation of Urban and Rural Public Resources in Luzhou City Based on Multi source Remote Sensing Data - Bing Xiao; Dan Xie; Ze Wang; Tao Ji; Ming Zeng; Jianyu Chen; Jiangjun Chen (SHS Web of Conferences)
Population is an important basis for land and resource planning, and optimising the allocation of urban and rural public resources is conducive to the development of the regional economy and the protection of the regional ecological environment. Existing studies have mostly adopted the field research method, which mainly relies on researchers’ field visits to the population and public resources in the study area, and the data obtained by this method are relatively accurate, but only small-scale studies can be carried out, and it is difficult for researchers to grasp the overall state of the regional population and urban and rural public resources as a whole. This study is mainly based on multi-source nighttime light remote sensing data to analyse the population distribution and urban and rural public resources development in Luzhou City, Sichuan Province from 2012 to 2020, and the results of the study show that: 1.The total population of Luzhou City in 2020 is 314,100 more than the resident population of Luzhou City in the regression compared with the statistical data of Luzhou City, and the relative error is 7.38%, which shows that the overall accuracy of this study is high. 2. Luzhou city overall population, economy and public resources rapid development of the region is more dense, and shows the phenomenon of spatial aggregation. Good population development and balanced allocation of urban and rural public resources will be conducive to promoting the rapid development of the regional economy and providing sustainable power for regional development.